SUNDANESE ETHNOMATHEMATICS: MATHEMATICAL ACTIVITIES IN ESTIMATING, MEASURING, AND MAKING PATTERNS - Dedi Muhtadi; Sukirwan Sukirwan; Warsito Warsito; Rully Charitas Indra Prahmana (Journal on Mathematics Education, 2017)
Mathematics is a form of culture integrated in all aspects of society, wherever there are, including the sundanese ethnic communities. This enables the mathematical concepts embedded in cultural practices and recognizes that all people develop a special way of doing mathematics called ethnomathematics activities. Sundanese ethnomathematics is mathematics in sundanese culture implemented in community activities. Sundanese ethnic sundanese people living in the area of West Java Indonesia, speaking sundanese language, and having activitiesÂ  reflecting sundanese culture. Sundanese ethnomathematics in this study has three activities, namely estimating, measuring, and making patterns appearing in the activities in term of kibik (a unit for measuring volume), bata (a unit for measuring surface area), and path pihuntuan (a model of cane work).DOI:Â http://dx.doi.org/10.22342/jme.8.2.4055.185-198